Relationship between carotid intima-media thickness, physical activity, sleep quality, metabolic/inflamatory profile, body fatness, smoking and alcohol consumption in young adults - Maillane-vanegas, Santiago (2017)
AbstractAIM The aim of this longitudinal study was to analyze the relationship between sleep disorder and intima-media thickness.METHOD Baseline measurements included carotid intima-media thickness, assessed by an ultrasound device; questionnaires about sleep and other behavioral variables; physical activity was measured by pedometer; body fatness was estimated by Dual-Energy X-ray Absorptiometry; fasting glucose, lipid profile and C-reactive protein were collected.RESULTS The occurrence rate of sleep-related disorders was 47% (95%CI= 37.2%-56.7%). Carotid intima-media thickness was related to symptoms of insomnia (r= 0.328 [0.141 to 0.493]) and, after adjustments for potential confounders, the relationship between carotid intima-media thickness and insomnia remained statistically significant (β= 0.121 [95%CI= 0.017; 0.225]).CONCLUSIONS In young adults, sleep disorder was significantly related to premature increase in carotid intima-media thickness.